The Influence of Accounting Knowledge, Information Technology, and Government Support on the Use of Accounting Information on MSMEs in Tulung Melati Village, Bekri District, Central Lampung Regency - Putri Amelia Amanda; Any Eliza; Ghina Ulfah (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of accounting knowledge, information technology, and government support on the use of accounting information in MSMEs in Tulung Melati Village, Bekri District, Central Lampung Regency. The research employed a quantitative method through the distribution of questionnaires to 44 respondents. Data analysis was conducted using SmartPLS. The results of the study indicate that government support has a positive and significant effect on the use of accounting information, while accounting knowledge and information technology do not have a positive and significant effect on the use of accounting information. This research provides both theoretical and practical contributions in encouraging the use of accounting information as a basis for decision-making and financial management in MSMEs efficiently and sustainably. It is recommended that the government and MSME actors strengthen collaboration in training and financial system digitalization.